2008
DOI: 10.1038/ajh.2008.260
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol Treatment Reduces Serum Levels of Asymmetric Dimethylarginine and Improves Endothelial Dysfunction in Essential Hypertensive Patients

Abstract: The results of this study demonstrate that the improvement of endothelial dysfunction induced by nebivolol in hypertensive patients may be related to its effect on circulating ADMA levels. Although the mechanism by which nebivolol reduces circulating ADMA in hypertensive patients remains unclear, our ex vivo results suggest that the upregulation of DDAH2 expression may have a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 41 publications
7
53
0
1
Order By: Relevance
“…The endothelial effects of nebivolol are unique amongst beta-blockers and have been replicated in other studies. 121,122 Recent work by Vitale et al has suggested that nebivolol in combination with hydrochlorthiazide might at least be non-inferior to irbesartan with hydrochlorthiazide, perhaps giving some hope to beta-blockers in hypertension. 123 Indeed, a recent meta-analysis of 1,273 patients from 16 studies by Peller et al on the effects of beta-blockers on endothelial function in various groups of patients did shown some benefit, however the study did include somewhat homogenous groups of patients.…”
Section: Diuretics and Beta-blockersmentioning
confidence: 99%
“…The endothelial effects of nebivolol are unique amongst beta-blockers and have been replicated in other studies. 121,122 Recent work by Vitale et al has suggested that nebivolol in combination with hydrochlorthiazide might at least be non-inferior to irbesartan with hydrochlorthiazide, perhaps giving some hope to beta-blockers in hypertension. 123 Indeed, a recent meta-analysis of 1,273 patients from 16 studies by Peller et al on the effects of beta-blockers on endothelial function in various groups of patients did shown some benefit, however the study did include somewhat homogenous groups of patients.…”
Section: Diuretics and Beta-blockersmentioning
confidence: 99%
“…To evaluate the previously reported effect of ␤-AR blocker treatment on endogenous nitric oxide (NO) synthase (NOS) inhibitor ADMA in hypertensive patients, we determined circulating ADMA before and after treatment (21). To determine whether nebivolol attenuates impair microvascular flow during exercise by increased EC expression p47 phox NADPH oxidase subunit resulting in increased oxidative stress, we performed peripheral venous EC collection in the same subjects (n ϭ 25) as previously described (6).…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…In 14 out of 15 studies, the ischemia lasted for 5 min, in 1 study it was 4.5 min [9]. In 12 studies, the cuff was placed on the forearm and in 3 studies measurements was performed with cuff placed on the arm [10][11][12]. Six studies reported the number of observers who assessed FMD [9,10,[13][14][15][16].…”
Section: Fmd Measurementsmentioning
confidence: 99%